Experimental investigation of leakage flow in centrifugal blood pump - Aw, Chung Seng (2012)
The study of leakage flow is crucial in designing centrifugal blood pumps. High volumetric efficiency is achieved when the leakage flow is low. However, low leakage flow cause formation of thrombus, while too high a leakage flow causes high shear to blood resulting in hemolysis.